Negative moment region flexural strengthening system of RC T-beams with half-embedded NSM FRP rods: a parametric analytical approach. (18th August 2021) - Haryanto, Yanuar; Hu, Hsuan-Teh; Han, Ay Lie; Hsiao, Fu-Pei; Teng, Charng-Jen; Hidayat, Banu Ardi; Wariyatno, Nanang Gunawan
ABSTRACT: Fiber Reinforced Polymer (FRP) rods are considered to be the most effective in retrofitting to increase the strength of reinforced concrete (RC) structures through Near-Surface Mounted (NSM) technique. There are, however, frequent cases encountered by engineers where the embedment depth mandated by ACI 440.2 R-08 code is not achievable in the field implementation. It has also been discovered that it is more challenging to strengthen the negative moment region of concrete members in comparison with the positive region. This research was conducted to determine the behavior of RC T-beams strengthened in the negative moment region using half-embedded NSM FRP rods. The findings were associated with the Modified Compression Field Theory (MCFT) which was applied in the analytical models. The model proposed was validated through a comparison with previous experimental study that showed half-embedded NSM FRP was effective as another method in comparison with the conventional soffit strengthening systems in retrofitting RC T-beams in the negative moment region, and good agreement was obtained. After that, a parametric analysis was initiated to determine the influence of FRP rod diameters, the compressive strength of concretes, the ratio of steel reinforcement as well as the materials used for the FRP on the flexural behavior of strengthened beams.